Ancaman Global Reset dalam Bidang Teknologi Ketahanan Pangan dan Energi dalam Perspektif Hubungan Internasional - Agus Nilmada Azmi; Febri Dirgantara Hasibuan; Saifudin Asrori; Muhammad Isma’il; Faisal Nurdin Idris (Kopertais Wilayah I DKI Jakarta dan Banten, 2026)
This study aims to analyze the phenomenon of the Global Reset and its implications for food security and energy security from the perspective of international relations. The research employs a qualitative approach using a library research method through the analysis of academic literature, international organization documents, policy reports, and other relevant publications. The findings indicate that the Global Reset has generated various debates regarding the governance of global food, energy, and technology systems. In the field of food security, the debates focus on the development of alternative food sources, the application of biological technologies, and the influence of global actors within the global food system. In the energy sector, the transition toward renewable energy and the expansion of carbon markets reflect the complex dynamics of interests among states, international organizations, and global corporations. The study finds that food and energy security are shaped not only by technical factors but also by political, economic, and technological dynamics within the international system. Therefore, strengthening international cooperation is essential to address these global challenges in a more equitable and sustainable manner.